ANALISIS BEBAN KERJA DENGAN METODE FULL TIME EQUIVALENT UNTUK KEBUTUHAN TENAGA KERJA (Studi Kasus Pada Staff Produksi Di PT. Kampung Coklat) - Sekartadji, Dewi Indah; Kurniastuti, Tri (Universitas Islam Balitar, 2024)
This research was conducted from February to March 2023 which coincided with PT Kampung Chocolate, Plosorejo Village, Kademangan District, Blitar Regency, East Java. This study aims to describe the organizational structure and number of employees in the chocolate production division in PT Kampung Chocolate. Conducting workload analysis on the number of employees in the production department using full time equivalent analysis. In this study, a quantitative descriptive research method is used, which conducts a research approach by utilizing numbers that are then analyzed. Full time equivalent analysis is a method that calculates workload based on working time. This labor relationship analysis research obtained two conclusions this study was conducted on the definition of production which has a production staff of 17 employees and is divided into 6 divisions. in each division is already in the normal FTE Index and the manpower needs are in accordance with the normal FTE results